Investment and Prices in Kaldor’s Model of Income Distribution - Walsteijn, R. Ph.G. (Journal of Income Distribution®, 1993)
In the first part of this paper are restated the main differences separating the Keynesian from the neoclassical theory with respect to aggregate demand and national income. Next, Kaldor’s distribution theory is examined, with special attention paid to the role of the general price level. Kaldor has demonstrated that equilibrium growth, with full employment of productive resources, is not necessarily restricted by an insufficient adaptation of savings to investment. Given this framework, it becomes crucial that the relationship between prices and money wages is fixed by the level of aggregate demand. Taking several social, cultural, and institutional characteristics of modern capitalist societies into consideration, this full employment equilibrium breaks down. The results are different from Kaldor’s but seem to bring his analysis more into line with the Keynesian heritage.